Flexural Fracturing of a Cohesive Granular Layer - Melo-Hurtado, F (2012)
We report on the fracturing of cohesive granular materials subjected to a flexural deformation. A thin layer of glass beads or of flour is deposited on an unstretchable membrane to which flexion is imposed. We observe the formation of a periodic fracturing pattern whose characteristics are discussed in comparison with results previously obtained for an in-plane stretching. In particular, at a given relative humidity, the wavelength is observed to depend linearly on the layer thickness but to be independent of the grain size, although the smallest grains are clearly more cohesive. © 2012 American Physical Society.